Evaluation of Pro-inflammatory Markers Plasma C-reactive Protein and Urinary Prostaglandin-E2 Metabolite in Colorectal Adenoma Risk - Davenport, James R. (Mol Carcinog, 2015)
C-reactive protein (CRP) is a pro-inflammatory protein with potential as a biomarker in predicting colon cancer risk. However, little is known regarding its association with risk of colorectal adenomas, particularly by subtypes. We conducted a colonoscopy-based matched case-control study to assess whether elevated plasma CRP levels may be associated with colorectal adenoma risk and further whether this association may be modified by urinary prostaglandin E2 metabolite (PGE-M), a biomarker of systemic prostaglandin E2 production. Included in the study were 226 cases with a single small tubular adenoma, 198 cases with multiple small tubular adenomas, 283 cases with at least one advanced adenoma, and 395 polyp-free controls. No apparent association between CRP level and risk of single small tubular adenomas was found (p(trend)=0.59). A dose-response relationship with CRP level was observed for risk of either multiple small tubular adenomas (OR = 2.01, 95% CI = 1.10–3.68 for the highest vs lowest tertile comparison; p(trend) = 0.03) or advanced adenomas (OR = 1.81, 95% CI = 1.10–2.96 for the highest vs lowest tertile comparison; p(trend)= 0.02). In a joint analysis of CRP level and PGE-M, risk of multiple or advanced adenoma was greatest among those with highest levels of both CRP and PGE-M in comparison to those with low CRP and low PGE-M (OR = 3.72, 95% CI = 1.49–9.72). Our results suggest that elevated CRP, particularly in the context of concurrent elevated PGE-M, may be a biomarker of multiple or advanced adenoma risk in a screening age population.